Sex-specific and inter-individual differences in biomarkers of selenium status identified by a calibrated ELISA for selenoprotein P - Hybsier, Sandra (Redox Biol, 2016)
Selenoprotein P (SELENOP) is a liver-derived transporter of selenium (Se) in blood, and a meaningful biomarker of Se status. Se is an essential trace element for the biosynthesis of enzymatically-active selenoproteins, protecting the organism from oxidative damage. The usage of uncalibrated assays hinders the comparability of SELENOP concentrations and their pathophysiological interpretation across different clinical studies. On this account, we established a new sandwich SELENOP-ELISA and calibrated against a standard reference material (SRM1950). The ELISA displays a wide working range (11.6–538.4 µg/L), high accuracy (2.9%) and good precision (9.3%). To verify whether SELENOP correlates to total Se and to SELENOP-bound Se, serum samples from healthy subjects and age-selected participants from the Berlin Aging Study II were analyzed by SELENOP-ELISA and Se quantification. SELENOP was affinity-purified and its Se content was determined from a subset of samples. There was a high correlation of total Se and SELENOP concentrations in young and elderly men, and in elderly women, but not in young women, indicating a specific sexual dimorphism in these biomarkers of Se status in young subjects. The Se content of isolated SELENOP was independent of sex and age (mean±SD: 5.4±0.5). By using this calibrated SELENOP-ELISA, prior reports on pathological SELENOP concentrations in diabetes and obesity are challenged as the reported values are outside reasonable limits. Biomarkers of Se status in clinical research need to be measured by validated assays in order to avoid erroneous data and incorrect interpretations, especially when analyzing young women. The Se content of circulating SELENOP differs between individuals and may provide some important diagnostic information on Se metabolism and status.